The prevalence of depression and its related factors among taxi drivers in Tehran city during 2017-2018 - Faghir Gangi, Monireh; Nematollahi, Shahrzad (Archives of Men’s Health, 2020)
Background: Depression is amongst the most significant causes responsible for loss of life, worldwide. It also increases the likelihood of accidents which may lead to unpleasant outcomes. Aim: This paper was aimed to measure the prevalence and related factors of depression amongst taxi drivers in Tehran city, from 2017 to 2018. Methods: This cross-sectional study was conducted on 350 taxi drivers. Cluster sampling was applied. Standard questionnaires, including Beck-21 items questionnaire, to measure depression, and job satisfaction questionnaire (JDI), were applied. Statistical analyses were performed using SPSS version 24 using Odds Ratios (OR) by logistic regression models. Significant level was considered 5% at all analyses. Results: The prevalence of depression was 43.3% and mean (SD) of job satisfaction score was 188.1 (54), with a median and interquartile range (70±193) for the highest and lowest level of job satisfaction were 350 and 60, respectively. The odds of having depression were 2.2 times higher in drivers with low job satisfaction (OR=2.2; 95%CI:1.3,3.8), 6.2 times higher in drivers who reported bad/very bad economic status (OR=6.2; 95%CI:2.1,18.3), and 1.8 times higher in cigarette smokers ‎(OR=1.8; 95%CI:1.0,3.4). The odds also increased by 2.6 times in drivers who reported average self-rated health (OR=2.6; 95%CI: 1.5, 4.5), and by 10.1 times in drivers who reported bad self-rated health ‎ (OR=6.2; 95%CI: 1.5, 65.0). Furthermore, having a history of depression amongst first degree family members, increased the odds by 2.6 times‎ (OR=2.6; 95%CI: 1.5, 4.5). ‎ ‎ Conclusion: We found that 43% of taxi drivers in Tehran city suffer from varying degrees of depression. It seemed that cigarette smoking, family history of depression, job dissatisfaction, and poorer economic status were important contributors of depression in our investigation.